An ecological, multilingual approach to language learning with newly reunited refugee families in Scotland. (2022) - Cox, Sarah; Phipps, Alison
Abstract : Although academic literature and Scotland's refugee integration strategy recommend multilingual, decolonising approaches, language classes for refugees in Scotland usually focus only on the target language (English) and are predominantly teacher-led. This paper argues that newly reunited refugee families can be better supported through an ecological, multilingual approach by presenting empirical data from a five-month teaching study using qualitative methods (semi-structured interviews, observations, autoethnographic fieldnotes). Using Critical Participatory Action Research (CPAR) and decolonising methodology, the teacher/researcher became a learner of the participants' languages to explore the shift in learner/teacher power dynamics created through mutual language learning sessions as linguistic hospitality. The findings illustrate the participants' increased feelings of confidence and empowerment in their learning. The approach complements existing community language classes.